Safety of Oral Bisphosphonates in Moderate‐to‐Severe Chronic Kidney Disease: A Binational Cohort Analysis. (8th February 2021) - Robinson, Danielle E; Ali, M Sanni; Pallares, Natalia; Tebé, Cristian; Elhussein, Leena; Abrahamsen, Bo; Arden, Nigel K; Ben‐Shlomo, Yoav; Caskey, Fergus J; Cooper, Cyrus; Dedman, Daniel; Delmestri, Antonella; et al.
ABSTRACT: Bisphosphonates are the first‐line treatment for preventing fractures in osteoporosis patients. However, their use is contraindicated or to be used with caution in chronic kidney disease (CKD) patients, primarily because of a lack of information about their safety and effectiveness. We aimed to investigate the safety of oral bisphosphonates in patients with moderate to severe CKD, using primary‐care electronic records from two cohorts, CPRD GOLD (1997–2016) and SIDIAP (2007–2015) in the UK and Catalonia, respectively. Both databases were linked to hospital records. SIDIAP was also linked to end‐stage renal disease registry data. Patients with CKD stages 3b to 5, based on two or more estimated glomerular filtration rate measurements less than 45 mL/min/1.73 m 2, aged 40 years or older were identified. New bisphosphonate users were propensity score–matched with up to five non‐users to minimize confounding within this population. Our primary outcome was CKD stage worsening (estimated glomerular filtration rate [eGFR] decline or renal replacement therapy). Secondary outcomes were acute kidney injury, gastrointestinal bleeding/ulcers, and severe hypocalcemia. Hazard ratios (HRs) were estimated using Cox regression and Fine and Gray sub‐HRs were calculated for competing risks. We matched 2447 bisphosphonate users with 8931 non‐users from CPRD and 1399 users with 6547 non‐users from SIDIAP. Bisphosphonate use was associated with greater risk of CKD progression in CPRD (sub‐HR [95% CI]: 1.14 [1.04, 1.26]) and SIDIAP (sub‐HR: 1.15 [1.04, 1.27]). No risk differences were found for acute kidney injury, gastrointestinal bleeding/ulcers, or hypocalcemia. Hence, we can conclude a modest (15%) increased risk of CKD progression was identified in association with bisphosphonate use. No other safety concerns were identified. Our findings should be considered before prescribing bisphosphonates to patients with moderate to severe CKD. © 2020 The Authors. Journal of Bone and Mineral Research published byWiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).